Penerapan Skrinning Perkembangan Anak Usia 5-6 Tahun di RA Bunayya II - Anugrah Satria Darmawan; Febby Ardera Br. Ginting; Mivtahul Zannah; Terang Claudia Simanjuntak; Mutiara Firdausi An Tasya; Najwa Mawaddah (Lembaga Pengembangan Kinerja Dosen, 2026)
Early childhood growth and development detection is an important process to identify potential physical, cognitive, emotional, and social developmental disorders in children before the age of six, which can help prevent long-term health and educational problems. Developmental screening is an initial assessment activity conducted to determine a child’s level of development according to their age. This screening aims to detect early whether a child’s development is within normal limits or if there is a possibility of developmental delay. This study aims to examine the developmental screening of children aged 5–6 years at RA Bunayya II. The research method used is qualitative research. Data were collected through observation and interviews. The results of the study indicate that all children are in the category of Developing as Expected. This is shown by the predominance of “Yes” responses on the indicators of the Pre-Developmental Screening Questionnaire (KPSP), which include aspects of speech and language, gross motor skills, fine motor skills, as well as social-emotional development and independence.